Sustainable groundwater management through water quality index and geochemical insights in Valsad India - Keval H. Jodhani; Nitesh Gupta; Sanidhya Dadia; Harsh Patel; Dhruvesh Patel; Punyawi Jamjareegulgarn; Sudhir Kumar Singh; Upaka Rathnayake (Scientific Reports, 2025)
. This dominance pattern demonstrated that the weathering of minerals significantly influenced the groundwater. This study recommends remediation for areas with reduced water quality to address geogenic and anthropogenic contamination.
Keywords: Water Quality and Pollution Assessment; Groundwater and Isotope Geochemistry; Groundwater and Watershed Analysis